Persepsi Masyarakat Tani Terhadap Implementasi Program Pembelajaran Luar Sekolah - Mauliza, Erna (Diksi: Jurnal Pendidikan dan Literasi, 2022)
The purpose of this study is to describe the carrying capacity/ limiting understanding of the village community on the importance of continuing education for children; describe the solutions undertaken to the villages community's understanding of the importance of continuing education for children; and describe the perception of village community towards the implementation of out-of-school learning programs in Desa Rantau Bintang Kec. Bandar Pusaka Kab. Aceh Tamiang. The research method used is qualitative. Instruments used for interviews, observations and documentation. The results stated that 1) that education is important given to children so that they can grow and develop and can get a good life in the future. 2) By providing understanding to parents who provide education to their children must realize that success requires a process so that their children can develop over time. 3) Out-of-school programs are expected to help parents in educating and accompanying children to learn to achieve success in the future